2020
DOI: 10.25100/socolen.v46i2.7065
|View full text |Cite
|
Sign up to set email alerts
|

Cíxidos y dérbidos (Hemiptera) vectores putativos de fitoplasma del grupo 16Sr-IV

Abstract: Los fitoplasmas del grupo 16SrIV causan enfermedades tipo amarillamiento letal (STAL) en palmas a nivel mundial. El fitoplasma del amarillamiento letal del cocotero (ALC) se conoce como ‘Candidatus Phytoplasma palmae’ (16SrIV-A). Al igual que en el ALC, muchas enfermedades causadas por fitoplasma a nivel mundial, sus vectores no han sido identificados. El único vector del fitoplasma del ALC incriminado es Haplaxius crudus (Hemiptera: Cixiidae). El objetivo del presente estudio fue determinar la presencia del f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…For that reason, phytoplasma strains associated with LY are often referred to as members of group 16SrIV, subgroup A (Lee et al, 1998), instead of having a conventional scientific name, although 'Candidatus Phytoplasma palmae' has also been proposed as a name for the taxon (Bertaccini et al, 2022). So far, the cixiid planthopper Haplaxius crudus Van Duzee is the only proven vector of this phytoplasma subgroup (Dzido et al, 2020), nevertheless, additional putative vectors of group 16SrIV phytoplasmas have also been discovered (Brown et al, 2006;Ramos-Hernández et al, 2020;Fernández-Barrera et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…For that reason, phytoplasma strains associated with LY are often referred to as members of group 16SrIV, subgroup A (Lee et al, 1998), instead of having a conventional scientific name, although 'Candidatus Phytoplasma palmae' has also been proposed as a name for the taxon (Bertaccini et al, 2022). So far, the cixiid planthopper Haplaxius crudus Van Duzee is the only proven vector of this phytoplasma subgroup (Dzido et al, 2020), nevertheless, additional putative vectors of group 16SrIV phytoplasmas have also been discovered (Brown et al, 2006;Ramos-Hernández et al, 2020;Fernández-Barrera et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The adult H. crudus is a vector of the causative agent of lethal coconut yellowing (ALC), a highly destructive disease of coconut and ornamental palms in Florida and several countries in the Caribbean Basin region [1,3]. The lethal yellowing of the coconut palm is caused by the phytoplasma Candidatus Phytoplasma palmae, belonging to the group 16SrIV subgroup A [4,5]. Studies conducted by Cenipalma found that H. crudus is responsible for disseminating in palm plantations in Colombia, the pathogen causing Lethal Wilt (LW).…”
Section: Introductionmentioning
confidence: 99%